Microglia Ontology and Signaling - ElAli, Ayman; Rivest, Serge (Frontiers in Cell and Developmental Biology, 2016)
Microglia constitute the powerhouse of the innate immune system in the brain. It is now widely accepted that they are monocytic-derived cells that infiltrate the developing brain at the early embryonic stages, and acquire a resting phenotype characterized by the presence of dense branching processes, called ramifications. Microglia use these dynamic ramifications as sentinels to sense and detect any occurring alteration in brain homeostasis. Once a danger signal is detected, such as molecular factors associated to brain damage or infection, they get activated by acquiring a less ramified phenotype, and mount adequate responses that range from phagocyting cell debris to secreting inflammatory and trophic factors. Here we review the origin of microglia and we summarize the main molecular signals involved in controlling their function under physiological conditions. In addition, their implication in the pathogenesis of multiple sclerosis and stress is discussed.